Nuer Tonal inventory - Irina Monich (Studies in African Linguistics, 2020)
The tonal system of Nuer has been a matter of much uncertainty. Here we present empirical evidence in favor of a three toneme system with some typologically rare features. One of them is an intriguing case of allotony based on the phonation of the vowel: the High toneme has a falling allotone over modal vowels. Moreover, the Rising toneme has four allotones: a rising, a mid, a low and a falling allotone. The falling allotone of the Rising toneme also occurs only on modal vowels in specific contexts. We suggest that some of the allotonic variation is motivated by tonal contour simplification. We also point out the role of free variation in some of the allotonic alternations, and the constraints that put limits on the free variation between allotones.